Virtual HDR CyberKnife SBRT for Localized Prostatic Carcinoma: 5-Year Disease-Free Survival and Toxicity Observations - Fuller, Donald Blake; Naitoh, John; Mardirossian, George (Frontiers in Oncology, 2014)
PURPOSE Prostate stereotactic body radiotherapy (SBRT) may substantially recapitulate the dose distribution of high-dose-rate (HDR) brachytherapy, representing an externally delivered “Virtual HDR” treatment method. Herein we present 5-year outcomes from a cohort of consecutively treated Virtual HDR SBRT prostate cancer patients. METHODS Seventy-nine patients were treated from 2006 - 2009, 40 low-risk and 39 intermediate-risk, under IRB-approved clinical trial, to 38 Gy in 4 fractions. The planning target volume (PTV) included prostate plus a 2-mm volume expansion in all directions, with selective use of a 5-mm prostate-to-PTV expansion and proximal seminal vesicle coverage in intermediate-risk patients, to better cover potential extraprostatic disease; rectal PTV margin reduced to zero in all cases. The prescription dose covered > 95% of the PTV (V100 >= 95%), with a minimum 150% PTV dose escalation to create “HDR-like” PTV dose distribution. RESULTS Median pre-SBRT PSA level of 5.6 ng/mL decreased to 0.05 ng/mL 5 years out and 0.02 ng/mL 6 years out. At least one PSA bounce was seen in 55 patients (70%) but only 3 of them subsequently relapsed, Biochemical-relapse-free survival was 100% and 92% for low-risk and intermediate-risk patients, respectively, by ASTRO definition (98% and 92% by Phoenix definition). Local relapse did not occur, distant metastasis-free survival was 100% and 95% by risk-group, and disease-specific survival was 100%. Acute and late grade 2 GU toxicity incidence was 10% and 9%, respectively; with 6% late grade 3 GU toxicity. Acute urinary retention did not occur. Acute and late grade 2 GI toxicity was 0% and 1%, respectively, with no grade 3 or higher toxicity. Of patients potent pre-SBRT, 65% remained so at 5 years. CONCLUSIONS Virtual HDR prostate SBRT creates a very low PSA nadir, a high rate of 5-year disease-free survival and an acceptable toxicity incidence, with results closely resembling those reported post-HDR brachytherapy.